ANALISIS PENERIMAAN PAJAK RESTORAN DAN KONTRIBUSINYA DALAM MENINGKATKAN PAJAK DAERAH DI KABUPATEN BARITO UTARA KALIMANTAN TENGAH TAHUN 2021-2024 - Destavania Liyudza Harimah; Achmad Suhaili; Sarwani (Universitas Lambung Mangkurat, 2025)
The purpose of this study is to evaluate the effectiveness and contribution of restaurant taxes to Local Own-Source Revenue (PAD) in North Barito Regency, Central Kalimantan, for the period 2021–2024. Data were collected through interviews and documentation using a quantitative descriptive approach, and contribution and effectiveness formulas were used for analysis. The results of the investigation indicate that restaurant tax collection is quite successful, contributing between 5.26% and 12.20% to PAD and having an average effectiveness rate of above 120%. This study contributes theoretically to strengthening the role of local taxes in fiscal decentralization and serves as a reference for policy on tax management in the service sector.